The Notion of the Work of Art in Arthur Danto: Line of Reasoning and Methodology - Chrisikaki, Dafni (Conatus - Journal of Philosophy, 2018)
Arthur Danto sees the work of art under the dual perspective of Art itself as a production process, and of Philosophy of Art as a means of evaluation on the basis of Historicism. Using the methodological tool of "non-discrimination" between works of art and real objects, that after all are erceptually similar (the "Brillo Box" as a commercial object - the "Brillo Box" as an artistic object), I will argue that he open dialectical basis for the interplay of all the elements in Arthur Danto's theory is a fertile ground for discussion of potential questions and problems that arise.